¿Qué tan prevalentes son las lesiones osteomusculares en el campo de la informática? - Albán Villacís, Jorge Aurelio (2017)
Context: musculoskeletal problems related to the type of work are frequent occupational diseases worldwide; It is important to determine early the prevalence of musculoskeletal symptoms in office workers and develop strategies to prevent and reduce their occurrence.Objective: to determine the relationship between inadequate ergonomic postures and the appearance of musculoskeletal injuriesSubjects and methods: workers of administrative areas that use computers in the city of Quito, through a cross-sectional study applied in 114 office workers. Sociodemographic and labor data were collected. The exposure to inappropriate postures was determined by means of a questionnaire with graphics to receive the perceptions of the interviewee as well as the identification of adequate and inadequate postures that the subjects under study maintain. To assess health aspects, a questionnaire of musculoskeletal symptoms was used; The association between variables was analyzed with the x2 test and the prevalence odds ratio (POR) was estimated.Results: 65.8% of the interviewees presented musculoskeletal symptoms, with osteomuscular pain being more prevalent in men (57.3%) than in the group of women (42.7%). 50.7% of workers reported working more than 7 hours in front of the computer. In the last three months, symptomatology was reported in the back (36.7%), neck (33%) and right hand-wrist (9.6%). The POR for upper limb pain was 2.42 (CI 0.98-5.49) which, although it includes values lower than one, establishes a significant risk burden for the type of work performed by the evaluated. The other symptoms were not statistically significant.Conclusion: the administrative occupation requires repetitive movements of wrists and fingers, accompanied by a static contraction of the cervical and dorsal muscles, which are transformed over the years into muscle tension, thus increasing the risk of muscle injuries. skeletal (SCI) as observed in this study